Classical and quantum modifications of gravity - Kimpton, Ian (2013)
Einstein’s General Relativity has been our best theory of gravity for nearly a century, yet we know it cannot be the final word. In this thesis, we consider modifications to General Relativity, motivated by both high and low energy physics.